Effect Of Tungsten Carbide Tool On The Mechanical Properties Of Friction Stir Lap Welded Aluminium And Stainless Steel Alloy - Elavarasu, Vinoshan (IRC, 2021)
There is a high demand for an efficient method of assembling steel and aluminium, especially in sectors such as the automotive and transport industries.